Cross-modal plasticity in the deaf enhances processing of masked stimuli in the visual modality - Seema Prasad (Nature Portfolio, 2017)
Abstract Compensatory changes as a result of auditory deprivation in the deaf lead to higher visual processing skills. In two experiments, we explored if such brain plasticity in the deaf modulates processing of masked stimuli in the visual modality. Deaf and normal-hearing participants responded to targets either voluntarily or by instruction. Masked primes related to the response were presented briefly before the targets at the center and the periphery. In Experiment 1, targets appeared only at the foveal region whereas, in Experiment 2, they appeared both at the fovea and the periphery. The deaf showed higher sensitivity to masked primes in both the experiments. They chose the primed response more often and also were faster during congruent responses compared to the normal hearing. These results suggest that neuroplasticity in the deaf modulates how they perceive and use information with reduced visibility for action selection and execution.